Analisis Strategi Pengembangan Bisnis pada Budidaya Ikan Cupang Hias Menurut Perspektif Ekonomi Islam - M Hafiz Zulfa; Efni Anita; Neneng Sudharyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Strengths, weaknesses, opportunities and threats all need to be identified when running a betta fish business. To address this need, SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is used, which plays a key role in determining an organization's strategy. SWOT analysis is a systematic method for analyzing threats and opportunities to predict future environmental conditions and predict problems that may arise in the future. In conducting this research, we adopted qualitative research as a method. Qualitative research is a research method that explores detailed information in the form of interviews with betta fish farmers in Jambi and provides descriptive data. This study also produces data in the form of written and spoken words directly from people and behavior that can be observed. The strategy used in developing the ornamental Betta fish cultivation business in the research area uses the SO (Strength and Opportunities) strategy. This strategy uses the company's strengths to overcome threats. The SO strategy uses the company's internal strengths to avoid or reduce the impact of external threats. In an Islamic economic perspective, the process of determining development strategies for ornamental betta fish cultivation businesses must be based on Islamic law, such as not selling or producing prohibited goods, as well as being transparent in determining price. And the most important thing is that cultivators do not carry out actions that deviate from the teachings of the Islamic religion.